Characterization of chronic active multiple sclerosis lesions with sodium (23Na) magnetic resonance imaging—preliminary observations. (6th May 2021) - Eisele, Philipp; Kraemer, Matthias; Dabringhaus, Andreas; Weber, Claudia E.; Ebert, Anne; Platten, Michael; Schad, Lothar R.; Gass, Achim
Abstract: Background and purpose: There has been an increasing interest in chronic active multiple sclerosis (MS) lesions as a new magnetic resonance imaging (MRI) marker of disease progression. Chronic active lesions are characterized by progressive tissue matrix damage, axonal loss and chronic inflammation. Sodium ( 23 Na) MRI provides a biochemical marker of cell integrity and tissue viability in a quantitative manner. The aim of this study was to investigate with 23 Na MRI tissue abnormalities in chronic active lesions as indicators of tissue destruction. Methods: To identify chronic active lesions, two 3D magnetization‐prepared rapid acquisition gradient‐echo datasets obtained 12 months apart were processed using the voxel‐guided morphometry algorithm. Cross‐sectional 23 Na MRI was performed during the 12‐month follow‐up period. Total sodium concentration was calculated in chronic active lesions compared to shrinking, chronic stable and acute contrast‐enhancing lesions. Results: Overall, 70 MS lesions (21 chronic active, 10 shrinking, 29 chronic stable lesions, 10 acute contrast‐enhancing lesions) in 12 patients were included. Total sodium concentration in chronic active lesions (49.57 ± 8.47 mM) was significantly higher than in shrinking (42.16 ± 3.9 mM; p  = 0.03) and chronic stable lesions (39.92 ± 4.82 mM; p  < 0.001). Chronic active lesions showed similar sodium values compared to acute contrast‐enhancing lesions (48.06 ± 6.65 mM; p  = 0.97). No differences between shrinking and chronic stable lesions were observed ( p  = 0.89). Conclusion: High sodium values in chronic active MS lesions may be an indicator of ongoing inflammation and tissue damage. Abstract : The aim of this study was to investigate with sodium ( 23 Na) magnetic resonance imaging tissue abnormalities in chronic active multiple sclerosis lesions compared to shrinking, chronic stable and acute contrast‐enhancing lesions. Interestingly, chronic active lesions showed similar sodium values compared to acute contrast‐enhancing lesions. High sodium values in chronic active lesions may be an indicator of ongoing inflammation and tissue damage.